Hybrid systems combining manures and cover crops can substantially reduce nitrogen fertilizer use. Issue 6 (2nd July 2020) - Maltais-Landry, Gabriel; Crews, Timothy E.
ABSTRACT: Manures allow for nitrogen (N) and phosphorus (P) recycling but low N:P ratios result in P over-fertilization when applying manures to meet crop N demand. Such stoichiometric imbalances can result in inefficient use of non-renewable P resources as well as aquatic eutrophication. On average, P surpluses in wheat ( Triticum aestivum L.) and corn ( Zea mays L.) systems of the United States vary between 1.4 and 3.1 kg P per kg of plant-available nitrogen (PAN) applied. Hybrid systems combining manures and biological N2 -fixation from cover crops can limit P over-fertilization and reduce synthetic N fertilizer inputs. On average, about 40–48% of corn and 69–75% of wheat crop N demand could be met by manures and legume cover crops in the United States. However, the range of their possible N contribution to a specific system is wide given the variability in nutrient concentrations/availability and transfer to a subsequent crop. The adoption of hybrid systems is also limited by other constraints, most notably the spatial decoupling between animal and crop production.